Cultural Components of Sex Differences in Color Preference. Issue 4 (21st January 2021) - Davis, Jac T. M.; Robertson, Ellen; Lew‐Levy, Sheina; Neldner, Karri; Kapitany, Rohan; Nielsen, Mark; Hines, Melissa
Abstract : Preferences for pink and blue were tested in children aged 4–11 years in three small‐scale societies: Shipibo villages in the Peruvian Amazon, kastom villages in the highlands of Tanna Island, Vanuatu, and BaYaka foragers in the northern Republic of Congo; and compared to children from an Australian global city (total N  = 232). No sex differences were found in preference for pink in any of the three societies not influenced by global culture ( d s − 0.31–0.23), in contrast to a female preference for pink in the global city ( d  = 1.24). Results suggest that the pairing of female and pink is a cultural phenomenon and is not driven by an essential preference for pink in girls.